Architecture of devotion : James Goold and his legacies in colonial Melbourne (The Miegunyah Press, 2021)
The Architecture of Devotion: James Goold and His Legacies in Colonial Melbourne' honours the life and cultural contribution of Archbishop James Alipius Goold (1812-1886). Goold arrived in 1848 as the first Catholic bishop of the newly created diocese of Melbourne and quickly adapted to Australian colonial conditions, setting about establishing an extraordinary network of schools, churches and welfare institutions across Victoria. Beyond the immediate task of building bluestone, bricks and mortar, Goold carried a grand vision, sensing that Melbourne was on its way to becoming a grand international metropolis. A collector and man of refined taste, Goold not only adorned religious institutions with quality Baroque artwork, but he also amassed a unique book collection and private library that showcased his European cultural sensibilities. A companion to 'The Invention of Melbourne: A Baroque Archbishop and a Gothic Architect' (The Miegunyah Press, 2019, ISBN), The 'Architecture of Devotion' brings Goold to life as we follow him around the colony and witness how he shaped the fabric of Victorian suburbs and towns. These volumes have been supported by the Australian Research Council, which has recognised them as among the best research projects in Australia. The Invention of Melbourne was commended in the Victorian Community History Award 'History Publication Award', 2020.